Pengaruh Metode Joyfull Learning terhadap Keaktifan Siswa dalam Pembelajaran PAI di UPTD SDN 02 Mungka - Dini Anggraini; Hamdi Abdul Karim; Khairuddin Khairuddin; Eka Rizal (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
Joyfull learning means fun learning. The joyfull larning method is a learning method that is preferred by students which is comfortable, safe dan exciting so that learning runs effectively and efficiently. The problem with the researcher’s observations resulted in the conlusion that there was a lack of student activity in expressing their opinions in class, student were still lazy in participating in learning, some student preferred listening rather than reading due to students; lack of interest in reading in class. In this study, the aim was to find out the effect of the joyfull learning method on student activity in PAI learning at UPTD SDN 02 Mungka for class III students using the material Thanking Allah SWT. this research uses an experimental research methodology with a pre-experimental design type one-group pretest-posttest research design. This research carried out tests before and after being given treatment in the form of questinnaires to third grade students. The big influence of applying method with results of the t test calculation in the form of a paired sample t-test shows that the significant value is 0.030, which means less than 0.05, so H0 is rejected and Ha is accepted. This means that there is a significant difference in student activity before and after using the joyfull learning method.